2015
DOI: 10.1089/humc.2014.154
|View full text |Cite
|
Sign up to set email alerts
|

Ferret and Pig Models of Cystic Fibrosis: Prospects and Promise for Gene Therapy

Abstract: Large animal models of genetic diseases are rapidly becoming integral to biomedical research as technologies to manipulate the mammalian genome improve. The creation of cystic fibrosis (CF) ferrets and pigs is an example of such progress in animal modeling, with the disease phenotypes in the ferret and pig models more reflective of human CF disease than mouse models. The ferret and pig CF models also provide unique opportunities to develop and assess the effectiveness of gene and cell therapies to treat affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 147 publications
0
47
0
1
Order By: Relevance
“…Bacterial and host factors that lead to failed clearance of the infected airway are likely important for this transition, though this is difficult to test directly in murine pneumonia models, where the acute-to-chronic transition is not observed. In the following section we review what has been learned about this transition from infecting mice with agar-encapsulated P. aeruginosa, from characterizing new non-murine models of CF (such as the pig and ferret [81]), and from increasingly sophisticated analyses of patients chronically infected with this organism.…”
Section: Survival Of the Fittest: Adapted To Thrive In The Inflamed Lungmentioning
confidence: 99%
“…Bacterial and host factors that lead to failed clearance of the infected airway are likely important for this transition, though this is difficult to test directly in murine pneumonia models, where the acute-to-chronic transition is not observed. In the following section we review what has been learned about this transition from infecting mice with agar-encapsulated P. aeruginosa, from characterizing new non-murine models of CF (such as the pig and ferret [81]), and from increasingly sophisticated analyses of patients chronically infected with this organism.…”
Section: Survival Of the Fittest: Adapted To Thrive In The Inflamed Lungmentioning
confidence: 99%
“…Firstly, the effects of roscovitine on CF models (organoĂŻds [234], ferret [235–237] and pig [95–98, 237, 238] models of CF, P. aeruginosa infection animal models [238, 239]) should be investigated. Secondly, given the host directed antibacterial effects of roscovitine, its action on other pulmonary pathogens associated with CF, besides P. aeruginosa , [240–242], should be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, Croyle et al showed that gene transduction in mouse lungs with HD-AdV was maintained after a second administration conducted 28 days after the initial dosing [92]. Airway transduction with HD-AdV has also been demonstrated in larger animals, including the ferret [93] and pig [94], further supporting its potential for inhaled gene therapy applications.…”
Section: Gene Delivery Platformsmentioning
confidence: 99%
“…Of note, submucosal glands are the primary source of the airway mucus secretion in the human lungs [200] and plays critical roles in innate immunity by secreting antimicrobials [342]. A recent study also found an alternative chloride channel is present in the mouse lung that can compensate for the lack of CFTR activity [93]. …”
Section: Preclinical Modelsmentioning
confidence: 99%